Life cycle assessment (LCA) of a solar selective surface produced by continuous process and solar flat collectors - ÇİFTÇİOĞLU, GÖKÇEN ALEV (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Roll to roll (R2R) continuous production of solar selective surface, is a cost benefit method from the energy dispenses and investment point of view, therefore it is an innovative production way. Before innovative energy systems are introduced into the market, a thorough investigation of ecological aspect is necessary. Therefore, the purpose of this study is not only to perform a life cycle assessment (LCA) and demonstrate the advantage of the life cycle thinking selective surface production process, but also as to show the effect of this production method on the manufacturing process of solar flat collectors. LCA calculations for the continuous selective surface production process and a complete solar collector were performed with using the Ecoinvent database and the build in methods in SimaPro7.3: (1) Cumulative Energy Demand (CED); (2) Greenhouse Gas Protocol (GHG); (3) the Eco-indicator 99. To reflect the total quantity of primary energy needed to produce, use, and recycle/dispose of the produced selective surface including transportation, CED was used. CED reflects the energy demand over its entire lifecycle, and makes it possible to determine which phase consumes the most energy. In order to quantify the greenhouse gas amount, the GHG was chosen since it is the most widely used and trusted international accounting tool. At last, the environmental impact of the system in study was calculated using Eco-indicator 99 method. The CED analysis estimated a yearly demand of 7.91 TJ for 200,000 square meter net selective surface production. Further calculations also showed that the energy payback time for the innovative production is as short as 3-4 days. Cu sheet production showed the highest impact and resulted in having the highest energy demand. The coating process only requires 32% of the primary energy demand. It was found that the energy demand of the plant and the building were as low as 2%, whereas it had 20% of GHG emissions. Further the total CO2 equivalent was shown to be 0.3245 kg/m(2). At last, the LCA for a complete solar collector having 4 m(2) of solar surface produced by conventional batch system and continuous roll to roll selective surface system was compared. The results also showed that using the roll to roll production technology caused reductions on the environmental burden. The results of LCA for the production of a continuous selective surface and comparison of solar flat collectors using two different selective surface production technology were presented. The energy payback time for the roll to roll selective surface production was found to be 3-4 days. The continuous process technology was shown to have a lower impact than the conventional batch selective surface production. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: LCA; Solar collectors; Selective surface; Roll to roll; SYSTEMS